Liquid crystal polymer composition, liquid crystal polymer molded body, and electrical / electronic device

CN117157360BActive Publication Date: 2026-11-03OTSUKA CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280027621.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-15
Filing Date
2022-03-30
Publication Date
2026-11-03
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

现有液晶聚合物成型体在超声波清洗时易剥离导致起毛现象,产生微小粉体,且难以抑制颗粒产生,影响拍摄模块的接合性和摩擦系数,无法满足智能手机等设备的小型化和薄型化需求。

Method used

A composition of reinforcing materials containing liquid crystal polymers, fluoropolymers, and hydrophobic surface treatment agents is used to reduce the dynamic and static coefficients of friction and suppress particle generation by covering the surface of the reinforcing materials with a hydrophobic treatment layer.

Benefits of technology

It effectively suppresses particle generation in the components of the imaging module, reduces the dynamic and static friction coefficients, improves the bonding and durability of the liquid crystal polymer molded body, and meets the requirements of miniaturization and thinning of equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004485427480000061
    Figure BDA0004485427480000061
  • Figure BDA0004485427480000261
    Figure BDA0004485427480000261
Patent Text Reader

Abstract

The present invention relates to a liquid crystalline polymer composition capable of suppressing generation of particles and capable of reducing dynamic and static coefficients of friction when a component for a camera module is molded, a liquid crystalline polymer molded body using the same, and an electrical and electronic device having the same. The liquid crystalline polymer composition is characterized by containing a liquid crystalline polymer (A), a fluororesin (B), and a reinforcing material (C), at least a part of the surface of the reinforcing material (C) being covered with a treatment layer composed of a hydrophobic surface treatment agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal polymer composition, a liquid crystal polymer molded body using the liquid crystal polymer composition, and an electrical and electronic device having the liquid crystal polymer molded body. Background Technology

[0002] Liquid crystal polymers are used in various components due to their excellent mechanical strength, moldability, dimensional accuracy, chemical resistance, moisture resistance, and electrical properties. In particular, their excellent heat resistance and thin-walled moldability are being investigated for applications in precision instruments and other electronic components, such as imaging modules.

[0003] When small particles, dirt, dust, etc., adhere to the lens or image sensor, the optical properties of the imaging module deteriorate. To prevent this deterioration, the components of the imaging module are usually ultrasonically cleaned before assembly to remove small particles, dirt, dust, etc., adhering to the surface. However, it is known that in molded bodies made of liquid crystal polymers (liquid crystal polymer molded bodies), due to the high crystal orientation of the liquid crystal polymer, the surface of the molded body is easily peeled off. During ultrasonic cleaning, surface peeling occurs, resulting in fuzzing (fibrillation). Moreover, tiny powders (particles) are easily generated from the fibrillated parts, reducing productivity. Furthermore, due to the ease of fibrillation, the bonding with other components of the imaging module is poor. Therefore, Patent Document 1 proposes a liquid crystal polymer composition containing inorganic particles with a Mohs hardness of 2.5 or higher.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Publication No. 2017-513976 Summary of the Invention

[0007] The technical problem that the invention aims to solve

[0008] On the other hand, camera modules are being assembled into various models such as smartphones, and camera modules with driver mechanisms such as autofocus (AF) and optical image stabilization (OIS) mechanisms are becoming increasingly common. In recent years, due to the increasing number of cameras in each smartphone, in order to manufacture camera modules at low cost, new driver mechanisms such as integrating AF and OIS mechanisms are becoming widespread, and miniaturization and thinning of devices and components are underway.

[0009] When focusing on the components of the shooting module, the high pixel count exceeding 100 million pixels and high-magnification optical zoom have highlighted unprecedented technical issues, such as the increased weight of the shooting module due to the increased number of lenses and the larger size of the lenses themselves, and the increased stress caused by the new structure of the shooting module. In recent years, drop tests have been conducted on electronic devices such as tablet computers, mobile phones, and smartphones with shooting functions as a durability test. However, the increased weight and stress of the shooting module have led to an increase in the amount of dust (particles) due to contact between components. Moreover, since the generation of dust (particles) is directly related to product performance defects such as the intake of dust into the camera and the impact on the operation of the shooting module, reducing the amount of dust (particles) has also become a major problem. In addition, in order to operate the actuator mechanism as described above smoothly, it is necessary to endow the liquid crystal polymer molded body constituting these mechanisms with the function of suppressing dust (particles).

[0010] However, the molded body made from the liquid crystal polymer composition of Patent Document 1 cannot adequately impart the function of suppressing particles, and there is also the problem that the dynamic friction coefficient and static friction coefficient cannot be sufficiently reduced.

[0011] The present invention addresses the technical challenge of suppressing dust (particles) generated in the imaging module components used in the AF and OIS mechanisms as the frequency of device use increases.

[0012] That is, the present invention aims to solve the following problems: to provide a liquid crystal polymer composition that can suppress particle generation and reduce the coefficient of dynamic friction and the coefficient of static friction when used in a component for a camera module, a liquid crystal polymer molded body using the liquid crystal polymer composition, and an electrical and electronic device having the liquid crystal polymer molded body.

[0013] Technical solutions for solving technical problems

[0014] To solve the aforementioned technical problems, the inventors of this invention conducted repeated and in-depth research, and as a result discovered, the following liquid crystal polymer composition can achieve the effect of suppressing particle generation in components for imaging modules and reducing the coefficients of dynamic and static friction, thus completing this invention. This liquid crystal polymer composition contains: a liquid crystal polymer (A); a fluoropolymer (B); a reinforcing material (C) whose surface is at least partially covered by a treatment layer composed of a hydrophobic surface treatment agent; and, as needed, barium sulfate (D); and particulate carbon material (E). In other words, the key points of this invention are as follows.

[0015] Item 1: A liquid crystal polymer composition, characterized in that it comprises a liquid crystal polymer (A), a fluoropolymer (B), and a reinforcing material (C), wherein at least a portion of the surface of the reinforcing material (C) is covered by a treatment layer composed of a hydrophobic surface treatment agent.

[0016] Item 2: The liquid crystal polymer composition as described in Item 1, characterized in that: the hydrophobic surface treatment agent is an alkoxysilane represented by the following general formula (I).

[0017] R 1 n Si(OR 2 ) 4-n ...Formula (I)

[0018] In general formula (I), n represents any integer selected from 1 to 3, and R 1 R indicates alkyl, alkenyl, or aryl. 2 Indicates alkyl group.

[0019] Item 3: The liquid crystal polymer composition as described in Item 1 or Item 2, characterized in that the average particle size of the fluoropolymer (B) is 0.1 μm to 100 μm.

[0020] Item 4: The liquid crystal polymer composition as described in any one of Items 1 to 3, characterized in that the content of the fluoropolymer (B) is 0.1% to 30% by mass in 100% by mass of the total liquid crystal polymer composition.

[0021] Item 5: The liquid crystal polymer composition as described in any one of items 1 to 4, characterized in that the content of the reinforcing material (C) is 0.1% to 40% by mass in 100% by mass of the total polymer composition.

[0022] Item 6: The liquid crystal polymer composition as described in any one of items 1 to 5, characterized in that: the reinforcing material (C) contains at least one of a fibrous reinforcing material (C1) and a plate-like reinforcing material (C2).

[0023] Item 7: The liquid crystal polymer composition as described in Item 6, characterized in that the average fiber length of the fibrous reinforcing material (C1) is 1 μm to 300 μm.

[0024] Item 8: The liquid crystal polymer composition as described in Item 6 or 7, characterized in that the Mohs hardness of the fibrous reinforcing material (C1) is 2.5 or more and 5 or less.

[0025] Item 9: The liquid crystal polymer composition as described in any one of items 6 to 8, characterized in that the Mohs hardness of the plate-like reinforcing material (C2) is 1 or more and less than 2.5.

[0026] Item 10: The liquid crystal polymer composition as described in any one of items 6 to 9, characterized in that the mass ratio of the above-mentioned plate-shaped reinforcing material (C2) to the above-mentioned fibrous reinforcing material (C1) (plate-shaped reinforcing material (C2) / fibrous reinforcing material (C1)) is 0 to 1.

[0027] Item 11: The liquid crystal polymer composition as described in any one of items 6 to 10, characterized in that the reinforcing material (C) comprises both fibrous reinforcing material (C1) and plate-like reinforcing material (C2).

[0028] Item 12: The liquid crystal polymer composition as described in Item 11, characterized in that at least a portion of the surfaces of both the fibrous reinforcing material (C1) and the plate-like reinforcing material (C2) are covered by a treatment layer consisting of a hydrophobic surface treatment agent.

[0029] Item 13: The liquid crystal polymer composition as described in any one of items 1 to 12, characterized in that: the liquid crystal polymer (A) is a fully aromatic liquid crystal polymer.

[0030] Item 14: The liquid crystal polymer composition as described in any one of items 1 to 13, characterized in that: the liquid crystal polymer composition is used in the imaging module.

[0031] Item 15: A liquid crystal polymer molded body, characterized in that: the liquid crystal polymer molded body is a molded body of the liquid crystal polymer composition described in any one of Items 1 to 14.

[0032] Item 16: The liquid crystal polymer molded body as described in Item 15, characterized in that: the liquid crystal polymer molded body is a component for a camera module.

[0033] Item 17: An electrical and electronic device, characterized in that: the electrical and electronic device has a shooting function, and the electrical and electronic device has the liquid crystal polymer molded body described in Item 15 or Item 16.

[0034] Invention Effects

[0035] According to the present invention, a liquid crystal polymer composition that can suppress particle generation and reduce the coefficient of dynamic friction and the coefficient of static friction when used as a component for a camera module, a liquid crystal polymer molded body using the liquid crystal polymer composition, and an electrical and electronic device having the liquid crystal polymer molded body are provided. Detailed Implementation

[0036] Hereinafter, an example of a preferred embodiment of the present invention will be described. However, the following embodiments are merely examples. The present invention is not limited to any of the embodiments described below.

[0037] <Liquid Crystal Polymer Composition>

[0038] The liquid crystal polymer composition of the present invention contains a liquid crystal polymer (A), a fluoropolymer (B), and a reinforcing material (C) whose surface is covered by a treatment layer composed of a hydrophobic surface treatment agent. It may also contain barium sulfate (D), particulate carbon material (E), solid lubricant and other additives as needed.

[0039] Because the liquid crystal polymer composition of the present invention has the above-described structure, it can suppress particle generation when used in components for imaging modules. Furthermore, the liquid crystal polymer molded body obtained by molding the liquid crystal polymer composition of the present invention can reduce both the dynamic and static coefficients of friction.

[0040] The following describes the constituent components of the liquid crystal polymer composition of the present invention.

[0041] (Liquid Crystal Polymer (A))

[0042] The liquid crystal polymer composition of the present invention contains a liquid crystal polymer (A) (hereinafter sometimes referred to as "component (A)"). Liquid crystal polymer (A) refers to a melt-processable polymer having the property of forming an optically anisotropic molten phase; there is no particular limitation as long as it is a polymer referred to as a thermotropic liquid crystal polymer in this technical field. The optically anisotropic molten phase can be identified by conventional polarization inspection using orthogonal polarizers.

[0043] Liquid crystal polymer (A) is a polymer with a long and flat molecular shape and highly rigid molecular chains (called "mesogenic groups") along its long molecular chains. Furthermore, liquid crystal polymer (A) may have liquid crystal groups in either or both of the polymer backbone and side chains; however, if higher heat resistance is required, the resulting liquid crystal polymer molded body preferably has liquid crystal groups in the polymer backbone.

[0044] Examples of components (A) include liquid crystal polyester, liquid crystal polyesteramide, liquid crystal polyester ether, liquid crystal polyester carbonate, liquid crystal polyester imide, and liquid crystal polyamide. From the viewpoint of obtaining a liquid crystal polymer molded article with superior strength, liquid crystal polyester, liquid crystal polyesteramide, or liquid crystal polyamide are preferred as component (A). Furthermore, from the viewpoint of obtaining a liquid crystal polymer molded article with lower water absorption, liquid crystal polyester or liquid crystal polyesteramide are preferred as component (A), and liquid crystal polyester is more preferred.

[0045] More specifically, examples include liquid crystal polymers such as (A1) to (A6), with a preference for fully aromatic liquid crystal polymers obtained by using only aromatic compounds as raw material monomers. Liquid crystal polymers selected from these can be used alone as component (A), or two or more can be combined as component (A).

[0046] Examples include:

[0047] (A1) Liquid crystal polyester comprising the repeating unit shown in formula (1);

[0048] (A2) A liquid crystal polyester comprising the repeating unit shown in formula (2) and the repeating unit shown in formula (3);

[0049] (A3) A liquid crystal polyester comprising the repeating unit shown in formula (1), the repeating unit shown in formula (2) and the repeating unit shown in formula (3);

[0050] (A4) In (A1), a liquid crystal polyester amide or liquid crystal polyamide is formed by replacing part or all of the repeating unit shown in formula (1) with the repeating unit shown in formula (4).

[0051] (A5) In (A2), a liquid crystal polyesteramide or liquid crystal polyamide is formed by replacing part or all of the repeating unit shown in formula (3) with the repeating unit shown in formula (5) and / or the repeating unit shown in formula (6).

[0052] (A6) In (A3), a liquid crystal polymer such as a liquid crystal polyesteramide is formed by replacing part or all of the repeating unit shown in formula (3) with the repeating unit shown in formula (5) and / or the repeating unit shown in formula (6). The liquid crystal polymer selected therefrom can be used alone or in combination of two or more as liquid crystal polymer (A).

[0053]

[0054] In the formula, Ar 1 and Ar 4 Each of these can be used independently to represent 1,4-phenylene, 2,6-naphthodiyl, or 4,4-biphenylene. Ar 2 Ar 3 Ar 5 and Ar 6 Each can be independently represented as 1,4-phenylene, 2,6-naphthyl, 1,3-phenylene, or 4,4-biphenylene. Additionally, Ar... 1 Ar 2 Ar 3 Ar 4 Ar 5 and Ar 6 Some or all of the hydrogen atoms on the aromatic ring can be replaced by halogen atoms, alkyl groups, or aryl groups.

[0055] The repeating unit shown in formula (1) is a repeating unit derived from an aromatic hydroxycarboxylic acid. Examples of such aromatic hydroxycarboxylic acids include 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-hydroxy-2-naphthoic acid, 6-hydroxy-1-naphthoic acid, 4-hydroxybiphenyl-4-carboxylic acid, or aromatic hydroxycarboxylic acids in which some or all of the hydrogen atoms on the aromatic ring are replaced by alkyl, aryl, or halogen atoms.

[0056] The repeating unit shown in formula (2) is a repeating unit derived from an aromatic dicarboxylic acid. Examples of such aromatic dicarboxylic acids include terephthalic acid, phthalic acid, 4,4-diphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, or aromatic dicarboxylic acids in which some or all of the hydrogen atoms on the aromatic ring of these aromatic dicarboxylic acids are replaced by alkyl, aryl, or halogen atoms.

[0057] The repeating unit shown in formula (3) is a repeating unit derived from an aromatic diol. Examples of such aromatic diols include hydroquinone, resorcinol, naphthalene-2,6-diol, 4,4-biphenylene glycol, 3,3-biphenylene glycol, 4,4-dihydroxydiphenyl ether, 4,4-dihydroxydiphenyl sulfone, or aromatic diols in which some or all of the hydrogen atoms on the aromatic ring are replaced by alkyl, aryl, or halogen atoms.

[0058] The repeating unit shown in formula (4) is a repeating unit derived from an aromatic aminocarboxylic acid. Examples of such aromatic aminocarboxylic acids include 4-aminobenzoic acid, 3-aminobenzoic acid, 6-amino-2-naphthoic acid, or aromatic aminocarboxylic acids in which some or all of the hydrogen atoms on the aromatic ring of these aromatic aminocarboxylic acids are replaced by alkyl, aryl, or halogen atoms.

[0059] The repeating unit shown in formula (5) is a repeating unit derived from an aromatic amine having a hydroxyl group. Examples of such aromatic amines with a hydroxyl group include 4-aminophenol, 3-aminophenol, 4-amino-1-naphthol, 4-amino-4-hydroxydiphenyl, or aromatic hydroxyl amines in which some or all of the hydrogen atoms on the aromatic ring of these aromatic amines with a hydroxyl group are replaced by alkyl, aryl, or halogen atoms.

[0060] The repeating unit shown in formula (6) is a structural unit derived from an aromatic diamine. Examples of such aromatic diamines include 1,4-phenylenediamine, 1,3-phenylenediamine, or aromatic diamines in which some or all of the hydrogen atoms on the aromatic ring are replaced by alkyl, aryl, or halogen atoms.

[0061] Examples of alkyl groups exemplified as substituents in the above structural units include straight-chain, branched, or alicyclic alkyl groups with 1 to 10 carbon atoms, such as methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, hexyl, cyclohexyl, octyl, and decyl. Examples of aryl groups include phenyl and naphthyl groups with 6 to 10 carbon atoms. Examples of halogen atoms include fluorine, chlorine, bromine, and iodine.

[0062] Of component (A), liquid crystal polyester selected from at least one of (A1) to (A3) is preferred because it can produce liquid crystal polymer molded articles with better heat resistance and dimensional stability, and liquid crystal polyester of (A1) or (A3) is particularly preferred.

[0063] Component (A) preferably has a melt viscosity of 1.0 × 10⁻⁶, measured at a temperature 20°C to 40°C higher than its melting point. 3 mPa·s~1.0×10 5 Liquid crystal polymers with a melting viscosity of 1.0 × 10⁻⁶ mPa·s. For example, based on their heat distortion temperatures, liquid crystal polymers with a load flexural temperature above 260°C are classified as Type I, and those with a load flexural temperature above 210°C but below 260°C are classified as Type II. Type I liquid crystal polymers are measured at a temperature 30°C above their melting point, and Type II liquid crystal polymers are measured at a temperature 40°C above their melting point. The above melt viscosity can be determined using a capillary rheometer at a value of 1.0 × 10⁻⁶ mPa·s. 3 sec -1 The shear rate was obtained by measuring the viscosity through an orifice with a diameter of 1 mm and a length of 10 mm.

[0064] There are no particular restrictions on the shape of component (A) as long as it can be melted and mixed. For example, it can be any shape among powder, granules, and pellets.

[0065] The content of component (A) in the liquid crystal polymer composition of the present invention is preferably 40% to 98% by mass, more preferably 60% to 94% by mass, and even more preferably 70% to 90% by mass in 100% by mass of the total liquid crystal polymer composition.

[0066] (Fluoropolymer (B))

[0067] The liquid crystal polymer composition of the present invention contains a fluoropolymer (B) (hereinafter sometimes referred to as "component (B)"). Component (B) is a polymer having repeating units – (CF2-CF2)-, and may, for example, be a polymer with a perfluoroalkyl ether group – (C p F 2p Modified polytetrafluoroethylene resin of type 1 (p is an integer from 1 to 4) -O)- (p is an integer from 1 to 4).

[0068] Component (B) can be an article obtained by any method, such as suspension polymerization for obtaining molding powder or emulsion polymerization for obtaining fine powder. Alternatively, it can be an article obtained by reducing the molecular weight of high molecular weight polytetrafluoroethylene resin through thermal decomposition or radiation.

[0069] Component (B) is preferably a powder, with an average particle size preferably from 0.1 μm to 100 μm, more preferably from 1 μm to 50 μm, and even more preferably from 5 μm to 20 μm. By setting the average particle size within the above range, the coefficient of friction during sliding can be further reduced. The average particle size of component (B) can be determined by laser diffraction / scattering, and is the particle size at which the volume basis of the particle size distribution is accumulated by 50% (50% volume basis particle size), i.e., D. 50 (Median particle size). This volumetric baseline cumulative 50% particle size (D) 50 The particle size distribution is determined based on volume. In the cumulative curve with the total volume as 100%, the number of particles is calculated starting from the smallest particles, and the particle size is calculated at the point where the cumulative value reaches 50%.

[0070] The particle shape of component (B) can be any non-fibrous particles, such as spherical, columnar, plate-like, rod-like, cylindrical, blocky, or irregularly shaped particles, without any particular limitation. The particle shape of component (B) can be analyzed by observation, for example, using a scanning electron microscope (SEM).

[0071] In this invention, fibrous particles refer to particles in which, when the longest side of the smallest cuboid in the circumscribed cuboid (the smallest cuboid in the circumscribed cuboid) is defined as the major diameter L, the second longest side as the minor diameter B, and the shortest side as the thickness T (B > T), both L / B and L / T are 3 or greater. The major diameter L corresponds to the fiber length, and the minor diameter B corresponds to the fiber diameter. It should be noted that, preferably, both L / B and L / T are 5 or greater in fibrous particles. Non-fibrous particles refer to particles with L / B less than 3. Non-fibrous particles with L / B less than 3 and L / T greater than 3 are called plate-like particles.

[0072] Polytetrafluoroethylene resin (hereinafter sometimes referred to as "PTFE"), although classified as a thermoplastic resin, is generally unsuitable for injection molding due to its exceptionally high melt viscosity. Resin compositions with PTFE as the main component can be molded by compressing a mixture of resin powders and heating it above its melting point, causing the powders to fuse together (compression molding). High molecular weight PTFE is used in compression molding; however, when high molecular weight PTFE is compounded and melt-mixed with conventional thermoplastic resins, the resin composition loses its fluidity due to fibrillation and aggregation of PTFE, making melt mixing or injection molding impossible. Therefore, low molecular weight PTFE is used as the solid lubricant in thermoplastic resins for injection molding. Furthermore, since liquid crystal polymers are typically melt-mixed at temperatures near the melting point of PTFE and have low viscosity at melt, aggregation may occur if the molecular weight of the compounded and melt-mixed PTFE is too high.

[0073] Since the molecular weight of PTFE is related to its melt viscosity, the PTFE used as component (B) preferably has an MFR value of 5 g / 10 min or more, more preferably 10 g / 10 min or more, and even more preferably greater than 35 g / 10 min, measured under conditions of 372°C and a load of 5 kg. Furthermore, the MFR value of component (B) can be determined based on JIS K7210.

[0074] To suppress fibrillation and agglomeration, PTFE is sometimes calcined. Although the melting point varies depending on the molecular weight, the calcined body has a melting point of 320°C–330°C, while the uncalcined body has a melting point of 330°C–350°C. Therefore, the degree of calcination can be inferred by observing the melting point. In component (B), from the viewpoint of further suppressing agglomeration during molding, the melting point is preferably below 330°C, with a lower limit preferably of 320°C. The melting point of PTFE can be determined based on JIS-K7121.

[0075] The content of component (B) in the liquid crystal polymer composition of the present invention is preferably 0.1% to 30% by mass, more preferably 1% to 20% by mass, further preferably 5% to 18% by mass, and particularly preferably 7.5% to 15% by mass in 100% by mass of the total liquid crystal polymer composition. By setting the content of component (B) in the range of 0.1% to 30% by mass, the sliding properties can be further improved.

[0076] (Reinforcing material (C))

[0077] The liquid crystal polymer composition of the present invention contains a reinforcing material (C) (hereinafter sometimes referred to as "component (C)"). Component (C) is a powdered reinforcing material composed of particles; the particle shape is not particularly limited as long as the particles improve the strength and rigidity of the resin composition. For example, fibrous reinforcing material (C1) (hereinafter sometimes referred to as "component (C1)") composed of fibrous particles, or plate-like reinforcing material (C2) (hereinafter sometimes referred to as "component (C2)") composed of plate-like particles can be used as component (C1). Preferably, one or more of fibrous reinforcing materials (C1) and plate-like reinforcing materials (C2) are selected. The particle shape of component (C) can be analyzed, for example, by observation using a scanning electron microscope (SEM).

[0078] In this invention, fibrous particles refer to particles in which, when the longest side of the smallest cuboid in the circumscribed cuboid (the circumscribed cuboid) is defined as the major diameter L, the second longest side as the minor diameter B, and the shortest side as the thickness T (B > T), both L / B and L / T are 3 or greater. The major diameter L corresponds to the fiber length, and the minor diameter B corresponds to the fiber diameter. Additionally, plate-like particles refer to particles with L / B less than 3 and L / T greater than 3.

[0079] Specific examples of fibrous reinforcing materials (C1) include inorganic fibers such as carbon fiber, glass fiber, potassium titanate fiber, wollastonite fiber, aluminum borate, magnesium borate, calcium silicate, zinc oxide, basic magnesium sulfate, alumina fiber, silicon carbide fiber, and boron fiber; and organic fibers such as aramid fiber and polyphenylene benzoxazole (PBO) fiber, with inorganic fibers being preferred. These fibrous reinforcing materials (C1) can be used individually or in combination.

[0080] From the viewpoint of further reducing particle generation, the fibrous reinforcement material (C1) is preferably composed of particles with a Mohs hardness of 2.5 to 5, and more preferably at least one of potassium titanate fibers and wollastonite fibers. Mohs hardness is an index that indicates the hardness of a material; the material with lower hardness is defined as the one that is damaged when rubbed against itself.

[0081] From the viewpoint of further reducing particle generation, the average fiber length of the fibrous reinforcement material (C1) is preferably 1 μm to 300 μm, more preferably 1 μm to 200 μm, even more preferably 3 μm to 100 μm, and particularly preferably 5 μm to 50 μm. Furthermore, the average aspect ratio of the fibrous reinforcement material (C1) is preferably 3 to 200, more preferably 3 to 100, even more preferably 3 to 50, and particularly preferably 3 to 40.

[0082] As potassium titanate fibers, widely known fibers can be used, such as tetratitanate fibers, hexatitanate fibers, and octatitanate fibers. The size of the potassium titanate fibers is not particularly limited as long as it falls within the aforementioned range, with the average fiber length preferably being 1 μm to 50 μm, more preferably 3 μm to 30 μm, and even more preferably 3 μm to 20 μm. The average fiber diameter of the potassium titanate fibers is preferably 0.01 μm to 1 μm, more preferably 0.05 μm to 0.8 μm, and even more preferably 0.1 μm to 0.7 μm. Furthermore, the average aspect ratio of the potassium titanate fibers is preferably 10 or more, more preferably 10 to 100, and even more preferably 15 to 35. These fibrous reinforcing materials (C1) can also be commercially available, such as "TISMO D" (average fiber length 15μm, average fiber diameter 0.5μm) and "TISMO N" (average fiber length 15μm, average fiber diameter 0.5μm) manufactured by Otsuka Chemical Co., Ltd.

[0083] Wollastonite fibers are inorganic fibers formed from calcium metasilicate. The size of the wollastonite fibers is not particularly limited as long as it falls within the size range of the aforementioned fibrous reinforcing material (C1). The average fiber length is preferably 5 μm to 180 μm, more preferably 7 μm to 100 μm, and even more preferably 9 μm to 40 μm. The average fiber diameter of the wollastonite fibers is preferably 0.1 μm to 15 μm, more preferably 1 μm to 10 μm, and even more preferably 2 μm to 7 μm. Furthermore, the average aspect ratio of the wollastonite fibers is preferably 3 or more, more preferably 3 to 30, and even more preferably 3 to 15. These fibrous reinforcing materials (C1) can also be commercially available, such as "BISTAL W" (average fiber length 25 μm, average fiber diameter 3 μm) manufactured by Otsuka Chemicals Co., Ltd.

[0084] The average fiber length and average fiber diameter mentioned above can be determined by observation using a scanning electron microscope (SEM). The average aspect ratio (average fiber length / average fiber diameter) can be calculated from the average fiber length and average fiber diameter. For example, multiple fibrous reinforcement materials can be photographed using a scanning electron microscope (SEM), and 300 fibrous reinforcement materials can be randomly selected from the observed images to determine their fiber length and fiber diameter. Furthermore, the average fiber length is obtained by dividing the total fiber length by the number of fibers, and the average fiber diameter is obtained by dividing the total fiber diameter by the number of fibers.

[0085] Specific examples of plate-like reinforcing materials (C2) include mica, sericite, illite, talc, kaolin, montmorillonite, boehmite, montmorillonite, vermiculite, titanium dioxide, potassium titanate, potassium lithium titanate, potassium magnesium titanate, and boehmite. These plate-like reinforcing materials (C2) can be used individually or in combination. It should be noted that in this invention, "plate-like" includes not only plate-like forms but also flake-like and scaly forms.

[0086] From the viewpoint of further reducing particle generation, the plate-like reinforcing material (C2) is preferably a particle with a Mohs hardness of 1 or higher but less than 2.5, and more preferably talc.

[0087] Talc has the chemical composition of hydrated magnesium silicate, usually represented by the chemical formula 4SiO2·3MgO·2H2O, and typically exists as flaky particles with a layered structure. These talcs are also available in commercially available products.

[0088] From the viewpoint of further reducing particle generation, the average particle size of the plate-shaped reinforcing material (C2) is preferably 1 μm to 50 μm, more preferably 3 μm to 30 μm, even more preferably 3 μm to 25 μm, and particularly preferably 5 μm to 25 μm.

[0089] The average particle size of component (C2) can be determined by laser diffraction / scattering. Specifically, the average particle size of component (C2) is the particle size at which the volume reference cumulative 50% of the particle size distribution determined by laser diffraction / scattering (50% volume reference cumulative particle size), i.e., D. 50 (Median particle size). This volumetric baseline cumulative 50% particle size (D) 50 The particle size distribution is determined based on volume. In the cumulative curve with the total volume as 100%, the number of particles is calculated starting from the smallest particles, and the particle size at the point where the cumulative value reaches 50% is calculated.

[0090] In this invention, component (C) is a reinforcing material whose surface is covered by a treatment layer composed of a hydrophobic surface treatment agent, at least a portion of which is covered. It should be noted that the treatment layer preferably covers 50% or more of the surface of the reinforcing material, more preferably 80% or more. Of course, it is particularly preferred that the treatment layer covers the entire surface of the reinforcing material. Furthermore, without compromising its preferred physical properties, component (C) can be a mixture of a reinforcing material whose surface is covered by a treatment layer composed of a hydrophobic surface treatment agent and an untreated reinforcing material whose surface is not covered by the hydrophobic surface treatment agent.

[0091] Examples of hydrophobic surface treatment agents include silane coupling agents, titanium coupling agents, and aluminate coupling agents. Among these, silane coupling agents are preferred, and hydrophobic alkyl silane coupling agents are more preferred.

[0092] As a hydrophobic silane coupling agent, any silane coupling agent with a hydrolytic functional group having an alkyl, aryl, or other essentially hydrophobic functional group and a hydrolytic functional group capable of generating a group that can react with a hydrophilic group on the surface of the reinforcing material is acceptable. A representative example of such a hydrophobic alkyl silane coupling agent is, for example, an alkoxysilane represented by the following general formula (I).

[0093] R 1 n Si(OR 2 ) 4-n ...Formula (I)

[0094] In general formula (I), n represents any integer selected from 1 to 3, and R 1 This indicates an alkyl, alkenyl, or aryl group, which may also have substituents. In the presence of multiple R groups... 1 At that time, these R 1 They can be the same or different. 2 This refers to alkyl groups, which can have substituents, and the presence of multiple R groups... 2 At that time, these R 2 They can be the same or different.

[0095] As R 1 Examples of alkyl groups include heptyl, octyl, nonyl, decyl, dodecyl, hexadecyl, octadecyl, and eicosyl. From the viewpoint of further improving the impact resistance of the obtained liquid crystal polymer molded article, the number of carbon atoms in the aforementioned alkyl group is preferably 8 or more, more preferably 10 or more. There is no particular upper limit to the number of carbon atoms in the alkyl group; for example, it can be 20 or less.

[0096] These alkyl groups can have cyclic or branched structures. Generally, alkyl groups tend to be more hydrophobic with a higher number of carbon atoms in the straight chain. Alkyl groups can have 1 to 4 (preferably 1 to 3, more preferably 1) substituents at any position.

[0097] As R 1 Examples of alkenyl groups include vinyl and butenyl groups. These alkenyl groups can have cyclic or branched structures. Furthermore, the alkenyl group can have 1 to 4 (preferably 1 to 3, more preferably 1) of the following substituents at any position.

[0098] As R 1 Examples of aryl groups shown include phenyl and naphthyl groups. Furthermore, these aryl groups may have 1 to 4 (preferably 1 to 3, more preferably 1) of the following substituents at any position.

[0099] The above R 1The groups shown can each have substituents, as long as they do not impair hydrophobicity. Examples of substituents include hydrophobic substituents such as fluorine atoms and (meth)acryloyloxy groups.

[0100] In addition, R 1 The alkyl groups shown can have the aryl groups exemplified above as hydrophobic substituents. Additionally, R... 1 The aryl group shown can have alkyl groups as hydrophobic substituents.

[0101] As R 2 Examples of alkyl groups shown include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, hexadecyl, octadecyl, eicosyl, etc. Among these, the alkoxy group (OR) in the alkoxysilanes represented by general formula (I) is significant. 2 ) is a hydrolyzable group, therefore, from the perspective of hydrolysis, R 2 Preferably, it is a lower alkyl group with 4 or fewer carbon atoms, more preferably ethyl or methyl, and even more preferably methyl.

[0102] In the above general formula (I), n represents any integer selected from 1 to 3. From the viewpoint of further improving the reactivity and hydrophobicity of the surface of the reinforced material particles, n is preferably 1.

[0103] Specific examples of the aforementioned alkoxysilanes include methyltrimethoxysilane, ethyltrimethoxysilane, hexyltrimethoxysilane, heptyltrimethoxysilane, octyltrimethoxysilane, nonyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, eicosyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, hexyltriethoxysilane, heptyltriethoxysilane, octyltriethoxysilane, nonyltriethoxysilane, decyltriethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane, octadecyltriethoxysilane, eicosyltriethoxysilane, and phenyltriethoxysilane. These can be used individually or in combination of two or more.

[0104] In this invention, the degree of hydrophobicity of the surface treatment agent can be represented by treating the surface of a glass plate with the surface treatment agent and measuring the surface free energy of the treated surface. Alternatively, in this invention, the surface free energy can be calculated by uniformly applying a surface treatment agent diluted 10 times with methanol onto a glass plate, heating it at 85°C for 1 hour, and then heating it at 110°C for 1 hour, measuring the static contact angle between water and decane on the surface coated with the surface treatment agent, and then calculating the surface free energy. For example, the surface free energy of decyltrimethoxysilane is 28 mN / m, that of γ-epoxypropoxypropyltrimethoxysilane is 55 mN / m, and that of 3-aminopropyltriethoxysilane is 68 mN / m.

[0105] The surface treatment agent used in this invention is not particularly limited, but preferably the liquid crystal polymer has good thermal stability at the molding and processing temperature, stable physical and chemical properties, and a surface free energy of less than 50 mN / m when uniformly treated on a glass plate. It should be noted that the lower limit of the surface free energy is not particularly limited, but is preferably 1 mN / m. It should also be noted that even surface treatment agents with a surface free energy exceeding 50 mN / m can have their surface free energy reduced to below 50 mN / m by mixing two or more of them.

[0106] When the surface free energy of the surface treatment agent is higher than 50 mN / m, it is higher than that of the liquid crystal polymer (A). Sometimes, it is impossible to control the metal ions dissolved from the damaged surface due to the breakage of the reinforcing material (C) during mixing and molding, which may sometimes promote the hydrolysis of the liquid crystal polymer (A). Therefore, it is preferable to fill the liquid crystal polymer (A) with a reinforcing material (C) whose surface free energy is adjusted to be below 50 mN / m.

[0107] Furthermore, the oil absorption of the surface-treated reinforcing material (C) is preferably less than 130 ml / 100 g, and more preferably 80 ml / 100 g to 130 ml / 100 g.

[0108] When the oil absorption exceeds 130 ml / 100 g, the compatibility with the liquid crystal polymer (A) decreases sharply, the productivity decreases significantly, and there is sometimes a problem that the filling amount of the surface-treated reinforcing material (C) cannot be increased.

[0109] In addition, the oil absorption of the surface-treated reinforcing material (C) can be determined using the refined linseed oil method [JISK5101-13-1].

[0110] In this invention, as a surface treatment method for the reinforcing material (C), and as a method for pre-treating the surface of the reinforcing material (C) with a coupling agent, dry methods and wet methods are known, and either method can be used. The surface treatment concentration relative to the reinforcing material (C) is preferably 0.1% to 3.0% by mass, more preferably 0.5% to 1.5% by mass.

[0111] As a method for forming a treatment layer composed of a surface treatment agent on the surface of component (C), known surface treatment methods can be used. Surface treatment can be carried out, for example, by loading the reinforcing material into a device capable of high-speed stirring, such as a Henschel mixer, and spraying the surface treatment agent (in the case of a liquid) onto the reinforcing material while stirring, or by a dry method, such as dissolving the surface treatment agent in a solvent that promotes hydrolysis (e.g., water, alcohol, or a mixture thereof).

[0112] When treating the surface of the reinforcing material (C) used in this invention with a surface treatment agent, the amount of the surface treatment agent is not particularly limited. In the case of a dry method, for example, the surface treatment agent is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, further preferably 0.3 to 5 parts by mass, more preferably 0.5 to 3 parts by mass, and particularly preferably 0.8 to 1.2 parts by mass when spraying a solution of the surface treatment agent relative to 100 parts by mass of the reinforcing material (C).

[0113] By setting the amount of surface treatment agent within the above range, the adhesion to component (A) can be further improved.

[0114] In the liquid crystal polymer composition of the present invention, the particle shape is not particularly limited. However, when used in a camera module component, from the viewpoint of further reducing particles and further reducing the sliding width and / or sliding depth of the sliding surface, component (C) preferably contains both a fibrous reinforcing material (C1) and a plate-like reinforcing material (C2), more preferably both a fibrous reinforcing material (C1) with a Mohs hardness of 2.5 to 5 and a plate-like reinforcing material (C2) with a Mohs hardness of 1 to 2.5. In this case, at least a portion of the surface of at least one of the fibrous reinforcing material (C1) and the plate-like reinforcing material (C2) is covered by a treatment layer composed of a hydrophobic surface treatment agent. Of course, from the viewpoint of further reducing particles in the camera module component and further reducing the coefficient of dynamic and static friction, it is preferable that at least a portion of the surface of both the fibrous reinforcing material (C1) and the plate-like reinforcing material (C2) is covered by a treatment layer containing a hydrophobic surface treatment agent.

[0115] The content of component (C) in the liquid crystal polymer composition of the present invention is preferably 0.1% to 40% by mass, more preferably 5% to 35% by mass, and even more preferably 10% to 30% by mass in 100% by mass of the total liquid crystal polymer composition.

[0116] By keeping the content of component (C) in the range of 0.1% to 40% by mass, when used in components for imaging modules, it is possible to further suppress particle generation and further reduce the coefficients of dynamic and static friction.

[0117] Regarding the component (C) in the liquid crystal polymer composition of the present invention, the mass ratio of the plate-like reinforcing material (C2) to the fibrous reinforcing material (C1), i.e., the ratio of plate-like reinforcing material (C2) to fibrous reinforcing material (C1), is preferably 0 to 1, more preferably 0.01 to 0.8, further preferably 0.1 to 0.7, and particularly preferably 0.2 to 0.6. By setting the mass ratio of the plate-like reinforcing material (C2) to the fibrous reinforcing material (C1) in the range of 0 to 1, the generation of particles can be further suppressed.

[0118] The content of fibrous reinforcing material (C1) in the liquid crystal polymer composition of the present invention is preferably 0.1% to 40% by mass, more preferably 5% to 35% by mass, and even more preferably 10% to 30% by mass in 100% by mass of the total liquid crystal polymer composition.

[0119] By setting the content of fibrous reinforcing material (C1) within the above range, when used in components for imaging modules, it is possible to further suppress particle generation, further reduce the sliding width and / or sliding depth of the sliding surface, and further reduce the dynamic friction coefficient and static friction coefficient.

[0120] The content of the plate-like reinforcing material (C2) in the liquid crystal polymer composition of the present invention is preferably 0.1% to 40% by mass, more preferably 0.5% to 20% by mass, and even more preferably 2% to 10% by mass in 100% by mass of the total liquid crystal polymer composition.

[0121] By setting the content of the plate-shaped reinforcing material (C2) within the above range, when used in components for imaging modules, it is possible to further suppress particle generation, further reduce the sliding width and / or sliding depth of the sliding surface, and further reduce the dynamic friction coefficient and static friction coefficient.

[0122] (Barium sulfate (D))

[0123] The liquid crystal polymer composition of the present invention may contain barium sulfate (D) (hereinafter sometimes referred to as "component (D)") as needed. Examples of component (D) include precipitated barium sulfate (barite powder) obtained by crushing, washing to remove iron from a mineral called barite, and panning, as well as artificially synthesized precipitating barium sulfate. Precipitating barium sulfate allows for control of particle size depending on the synthesis conditions, enabling the production of fine barium sulfate with a low content of coarse particles. From the viewpoint of further reducing impurities and achieving a more uniform particle size distribution, precipitating barium sulfate is preferred.

[0124] Component (D) is preferably a powder, with an average particle size preferably of 0.01 μm to 50 μm, more preferably of 0.03 μm to 30 μm, further preferably of 0.05 μm to 5 μm, even more preferably of 0.1 μm to 1.2 μm, and particularly preferably of 0.2 μm to 0.8 μm. By controlling the average particle size within the above range, the coefficient of friction during sliding can be further reduced.

[0125] The average particle size of component (D) can be determined by laser diffraction / scattering. More specifically, the average particle size of component (D) is the particle size at which the volume basis of the particle size distribution is accumulated to 50% (50% volume basis particle size) as determined by laser diffraction / scattering, i.e., D. 50 (Median particle size). This volumetric baseline has a cumulative 50% particle size (D). 50 The particle size distribution is obtained based on volume. In the cumulative curve with the total volume as 100%, the number of particles is calculated starting from the smallest particles, and the particle size at the point where the cumulative value reaches 50%.

[0126] The particle shape of component (D) is not particularly limited as long as it is a non-fibrous particle, such as spherical, columnar, plate-like, rod-like, cylindrical, blocky, or irregularly shaped, but spherical or irregular shapes are preferred. The particle shape of barium sulfate can be analyzed, for example, by observation using a scanning electron microscope (SEM). Component (D) can also be surface-treated. Examples of treatment agents include coating agents, dispersants, and modifiers, specifically fatty acids, waxes, nonionic surfactants, epoxy compounds, isocyanate compounds, silane compounds, titanate (ester) compounds, phosphorus compounds, aluminum salts such as alumina, silicates such as silicon dioxide, and titanium salts such as titanium dioxide. These treatment agents can be used alone or in combination of two or more.

[0127] The content of component (D) in the liquid crystal polymer composition of the present invention is preferably 1% to 30% by mass, more preferably 1% to 20% by mass, further preferably 1% to 15% by mass, particularly preferably 1% to 7% by mass, and most preferably 1.5% to 2.5% by mass, within 100% by mass of the total liquid crystal polymer composition. By setting the content of component (D) in the range of 1% to 30% by mass, the formation of particles can be further reduced.

[0128] (Partial carbon materials (E))

[0129] The liquid crystal polymer composition of the present invention may contain particulate carbon material (E) (hereinafter sometimes referred to as "component (E)") as needed. As component (E), it is a material used for purposes such as ensuring the light-shielding performance of liquid crystal polymer molded articles such as parts for imaging modules, and commonly available materials used in coloring the resin composition may be appropriately used.

[0130] Specific examples of particulate carbon material (E) may include graphite; carbon blacks such as acetylene black, furnace black, lampblack, pyrolytic black, channel black, drum black, and disc black; carbon nanotubes; and carbon fibers. From the viewpoint of further improving the light-shielding properties of the liquid crystal polymer molded from the liquid crystal polymer composition of the present invention, carbon black is preferred as the particulate carbon material (E). It should be noted that these particulate carbon materials (E) may be used alone or in combination.

[0131] In this invention, the primary particle size of the particulate carbon material (E) is preferably 10 nm or more and 50 nm or less.

[0132] When the primary particle size of the particulate carbon material (E) is 10 nm or more and 50 nm or less, the particulate carbon material (E) is easily dispersed into the liquid crystal polymer composition when manufacturing the liquid crystal polymer composition of the present invention or a liquid crystal polymer molded from the liquid crystal polymer composition of the present invention. Furthermore, since the surface resistivity of the liquid crystal polymer molded from the liquid crystal polymer composition of the present invention can be sufficiently reduced, the increase in charge in the liquid crystal polymer molded body can be further suppressed. In the liquid crystal polymer molded body obtained in this way, the surface resistivity within the surface of the liquid crystal polymer molded body is easily and uniformly achieved. As a result, the increase in charge can be suppressed at any position within the surface of the liquid crystal polymer molded body. The primary particle size of the particulate carbon material (E) is preferably 15 nm or more and 45 nm or less, more preferably 20 nm or more and 45 nm or less.

[0133] In this invention, the primary particle size of the particulate carbon material (E) can be the arithmetic mean particle size (number mean), which is the average of the primary particle sizes measured by transmission electron microscopy.

[0134] In this invention, the DBP oil absorption of the particulate carbon material (E) is preferably 90 cm³. 3 / 100g or more, preferably 550cm 3 / less than 100g.

[0135] The higher the DBP oil absorption of the particulate carbon material (E), the more voids are near the surface of the particulate carbon material (E). When there are more voids near the surface of the particulate carbon material (E), the particulate carbon material (E) can easily capture and connect with each other in the liquid crystal polymer composition.

[0136] The DBP oil absorption of particulate carbon material (E) is 90 cm. 3 When the weight is above 100g, the liquid crystal polymer molded body formed from the liquid crystal polymer composition can easily conduct electricity sufficiently at the bonding portion of the particulate carbon material (E). As a result, the surface resistivity of the molded body can be further reduced sufficiently. Therefore, the increase of charge in the molded body can be further suppressed sufficiently. However, when the DBP oil absorption of the particulate carbon material (E) is too high, there are too many voids near the surface of the particulate carbon material (E), and the particulate carbon material (E) in the liquid crystal polymer composition can easily become firmly trapped together. In addition, when the liquid crystal polymer (A), fluoropolymer (B), reinforcing material (C), particulate carbon material (E), and additives added as needed are melt-blended, the melt viscosity of the mixture sometimes becomes high. As a result, it is sometimes difficult to blend the mixture and difficult to manufacture the liquid crystal polymer composition. When the DBP oil absorption of the particulate carbon material (E) is 550cm³, 3 When the volume is less than 100g, the viscosity of the mixture of liquid crystal polymer (A), fluoropolymer (B), reinforcing material (C), particulate carbon material (E), and additives added as needed, does not become excessively high during melt blending. As a result, the mixture is easy to granulate, making it easier to manufacture the liquid crystal polymer composition of the present invention. The DBP oil absorption of the particulate carbon material (E) is preferably 90cm³. 3 / 100g or more, preferably 92cm 3 / 100g or more, preferably 550cm 3 / less than 100g, more preferably 525cm 3 / less than 100g.

[0137] In this invention, the oil absorption of DBP is measured using a dibutyl phthalate absorber based on JIS K 6221.

[0138] In this invention, the BET specific surface area of ​​the particulate carbon material (E) is preferably 75 m². 2 / g or more 1500m 2 / g or less, preferably 95m2 / g or more 1350m 2 / g or less, more preferably 100m 2 / g or more 1300m 2 / g or less.

[0139] In this invention, the BET surface area can be calculated using the BET method by measuring the amount of nitrogen adsorbed at liquid nitrogen temperature using a BET surface area analyzer. For example, the AccuSorb2100E manufactured by Micromeritics can be used as the BET surface area analyzer.

[0140] When the BET specific surface area of ​​the particulate carbon material (E) is above the aforementioned lower limit, the liquid crystal polymer molded body formed from the liquid crystal polymer composition of the present invention can easily and sufficiently conduct electricity at the connecting portion of the particulate carbon material (E). As a result, the surface resistivity of the liquid crystal polymer molded body can be further reduced. Therefore, the increase of charge in the molded body can be further suppressed.

[0141] When manufacturing the liquid crystal polymer composition and molded body of the present invention, when the BET specific surface area of ​​the particulate carbon material (E) is below the aforementioned upper limit, the melt viscosity of the mixture of the liquid crystal polymer (A), fluoropolymer (B), reinforcing material (C), particulate carbon material (E), and additives added as needed, does not become excessively high. As a result, the mixture becomes easier to mix, and the liquid crystal polymer composition of the present invention can be manufactured more easily.

[0142] The content of component (E) in the liquid crystal polymer composition of the present invention is preferably in the range of 0.1% to 5.0% by mass, more preferably 1.0% to 4.5% by mass, and even more preferably 2.0% to 4.0% by mass, within 100% by mass of the total liquid crystal polymer composition. When the content of component (E) is too low, the blackness of the obtained liquid crystal polymer composition is sometimes reduced, and the light-blocking property cannot be adequately ensured.

[0143] Furthermore, when the content of component (E) is too high, during melt mixing, the agglomerates (small nodular protrusions formed by the aggregation of particulate carbon material (E)) float in the resin formed by the low viscosity molten liquid crystal polymer. The distribution during mixing is difficult, the possibility of poor dispersion increases, stress concentration in the agglomerates becomes the starting point of failure, and the mechanical strength of the liquid crystal polymer molded body may be significantly reduced, making it difficult to achieve the original purpose.

[0144] By setting the content of component (E) in the range of 0.1% to 5.0% by mass, the dispersibility in the liquid crystal polymer composition can be further improved.

[0145] (Solid lubricant)

[0146] In the liquid crystal polymer composition of the present invention, a solid lubricant other than PTFE (hereinafter sometimes referred to as "solid lubricant") may be contained, within a range that does not impair its preferred properties.

[0147] Examples of solid lubricants include polyolefin resins such as low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, and ultra-high molecular weight polyethylene, as well as silicone resins, graphite, molybdenum disulfide, tungsten disulfide, and boron nitride. These can be combined with one or more of these compounds.

[0148] The content of solid lubricant in the liquid crystal polymer composition of the present invention is preferably 0.5% to 10% by mass, more preferably 1% to 7% by mass, in 100% by mass of the total liquid crystal polymer composition.

[0149] (Other additives)

[0150] The liquid crystal polymer composition of the present invention may contain other additives within a range that does not impair its preferred physical properties. Examples of other additives include inorganic fillers other than reinforcing material (C) and barium sulfate (D) (e.g., calcium carbonate, mica, sericite, illite, talc, kaolin, montmorillonite, boehmite, montmorillonite, vermiculite, palygorskite, pyrophyllite, halloysite, diatomaceous earth, titanium dioxide, etc.); laser direct forming additives (e.g., MgAl2O4, ZnAl2O4, FeAl2O4, CuFe2O4, CuCr2O4, MnFe2O4, etc.). O4, NiFe2O4, TiFe2O4, FeCr2O4, MgCr2O4, etc.); conductive fillers other than particulate carbon materials (E) (e.g., metal particles (e.g., aluminum sheets), metal fibers, metal oxide particles, carbon fibers, ionic liquids, surfactants, etc.); antistatic agents (e.g., anionic antistatic agents, cationic antistatic agents, nonionic antistatic agents, etc.); antioxidants and heat stabilizers (e.g., hindered phenols, hydroquinones, phosphites, sulfides, and their substitutes). (etc.); UV absorbers (e.g., resorcinols, salicylates, benzotriazoles, benzophenones, triazines, etc.); light stabilizers (e.g., hindered phenols, hindered amines, etc.); weathering agents; lightfastness agents; mold release agents (e.g., higher fatty acids, higher fatty acid esters, higher fatty acid amides, higher fatty acid metal salts (where higher fatty acids refer to fatty acids with 10-25 carbon atoms), fatty acids, fatty acid metal salts, etc.); lubricants; flow improvers; plasticizers (e.g., polyester plasticizers, glycerin plasticizers, etc.). The liquid crystal polymer composition of the present invention may contain one or more of the following: polycarboxylic acid ester plasticizers, phosphate ester plasticizers, polyalkylene glycol plasticizers, epoxy plasticizers; impact modifiers; flame retardants (e.g., phosphazene compounds, phosphate esters, condensed phosphate esters, inorganic phosphorus-based, halogen-based, organosilicon-based flame retardants, metal oxide-based flame retardants, metal hydroxide-based flame retardants, organometallic salt-based flame retardants, nitrogen-based flame retardants, boron compound-based flame retardants, etc.); anti-drip agents; nucleating agents; dispersants; vibration damping agents; neutralizing agents; anti-blocking agents, etc. From the viewpoint of obtaining molded articles with superior adhesion to adhesives such as epoxy resins and further suppressed particle formation, the liquid crystal polymer composition of the present invention preferably contains heat stabilizers and / or light stabilizers, wherein preferably it contains at least one compound selected from hindered phenols, hindered amines, and thioethers, more preferably it contains at least one compound selected from hindered phenols and hindered amines. From the viewpoint of obtaining molded articles with superior adhesion to adhesives such as epoxy resins, the above-mentioned compounds preferably have amide groups and / or amino groups.

[0151] When the liquid crystal polymer composition of the present invention contains other additives, there is no particular limitation on the amount of such additives, as long as it does not impair the preferred properties of the liquid crystal polymer composition of the present invention. Preferably, it is 10% by mass or less, and more preferably 5% by mass or less, out of a total of 100% by mass of the liquid crystal polymer composition.

[0152] <Method for manufacturing liquid crystal polymer compositions>

[0153] The liquid crystal polymer composition of the present invention can be manufactured by heating and mixing (especially melt mixing) a mixture comprising a liquid crystal polymer (A), a fluoropolymer (B), a reinforcing material (C) whose surface is covered by a treatment layer consisting of a hydrophobic surface treatment agent, and, if necessary, further containing barium sulfate (D), particulate carbon material (E), a solid lubricant, and other additives.

[0154] Melt blending can be performed using known melt blending equipment such as twin-screw extruders. Specifically, it can be manufactured by (1) premixing the components using a mixer (drum, Henschel mixer, etc.), performing melt blending using a melt blending equipment, and granulating using a granulation equipment (granulator, etc.); (2) preparing a masterbatch of the required components, mixing other components as needed, performing melt blending using a melt blending equipment, and granulating; (3) feeding the components to a melt blending equipment for granulation, etc.

[0155] The processing temperature during melt blending is not particularly limited as long as it is sufficient to melt the liquid crystal polymer (A). Typically, the barrel temperature of the melt blending apparatus used for melt blending is adjusted to this range. In this way, the liquid crystal polymer composition of the present invention that achieves the desired effect can be produced.

[0156] <Manufacturing methods and applications of liquid crystal polymer molded articles>

[0157] The liquid crystal polymer composition of the present invention can be molded according to the type, application, shape, etc. of the target liquid crystal polymer molded body using known resin molding methods such as injection molding, insert molding, compression molding, blow molding, and blow forming to form a liquid crystal polymer molded body. Injection molding and insert molding are preferred molding methods. Furthermore, molding methods combining the above-mentioned molding methods can also be used.

[0158] When the liquid crystal polymer molded body obtained by molding the liquid crystal polymer composition of the present invention is used as a component for a camera module, the generation of particles can be suppressed. Furthermore, the liquid crystal polymer molded body of the present invention can also reduce the coefficient of dynamic friction and the coefficient of static friction.

[0159] Liquid crystal polymer molded bodies formed using the liquid crystal polymer composition of the present invention can be applied to components used in the manufacture of electronic components for precision instruments. As components having the above-described liquid crystal polymer molded bodies, they are suitable for manufacturing electronic components for sliding parts that slide alongside other components, such as components selected from connectors, antennas, switches, relays, and imaging modules. In particular, the liquid crystal polymer molded bodies of the present invention are especially suitable for manufacturing optical electronic components (components for imaging modules) constituting imaging modules because they can prevent the reduction of optical properties caused by fibrillation on the surface of the liquid crystal polymer molded body and / or particles in the imaging module components.

[0160] Examples of optical and electronic components constituting the shooting module include the lens barrel (lens mounting part), spacer, mounting bracket (part that mounts the lens barrel and fixes it to the substrate), base, lens barrel, CMOS (image sensor) frame, shutter, shutter plate, shutter axis, aperture ring, brake (part that holds the lens), wing plate, yoke, etc.

[0161] The electrical and electronic device of the present invention has the above-described liquid crystal polymer molded body and has a camera function. In particular, the electrical and electronic device of the present invention is suitable for use as a smartphone or tablet computer terminal equipped with a camera function.

[0162] Example

[0163] The present invention will now be described in detail based on embodiments and comparative examples, but the present invention is not limited thereto. It should be noted that the raw materials used in these embodiments and comparative examples are as follows.

[0164] (Liquid Crystal Polymer (A))

[0165] Liquid crystal polymer: Fully aromatic type I, melt viscosity 2.0 × 10⁻⁶ 4 mPa·s (measured at 350°C), melting point 320°C, manufactured by Ueno Pharmaceutical Co., Ltd., trade name "UENO LCP A-6000"

[0166] (Fluoropolymer (B))

[0167] Polytetrafluoroethylene (PTFE) resin: average particle size 8μm, MFR value above 50g / 10min, melting point 324℃, manufactured by 3M, trade name "PTFE TF-9205"

[0168] (Barium sulfate (D))

[0169] Average particle size 0.28 μm, manufactured by Sakai Chemical Industry Co., Ltd., trade name "Precipitating Barium Sulfate B-31"

[0170] (other)

[0171] Untreated wollastonite fibers: average fiber length 9.3 μm, average fiber diameter 2.4 μm, aspect ratio 3.9.

[0172] Untreated potassium titanate fiber: average fiber length 15μm, average fiber diameter 0.5μm, aspect ratio 30, potassium hexatitanate fiber

[0173] Untreated talc: average particle size 19μm, manufactured by Fuji Talc Industry Co., Ltd., trade name "RG319"

[0174] (Partial carbon materials (E))

[0175] Carbon black: primary particle size 24nm, BET specific surface area 110m² 2 / g, DBP oil absorption 95cm 3 / 100g, manufactured by Mitsubishi Chemical Corporation, trade name "MA100RB"

[0176] (Determination of melt viscosity)

[0177] The melt viscosity of liquid crystal polymer (A) was measured using a melt viscosity measuring device (manufactured by Toyo Seiki Co., Ltd., trade name "CAPILLOGRAPH 1D") at a temperature 30°C higher than the melting point of liquid crystal polymer (A) and a shear rate of 1.0 × 10⁻⁶. 3 sec -1 Under the specified conditions, measurements were performed using a 1.0 mm Φ × 10 mm orifice.

[0178] (Average particle size of fluoropolymer (B) and barium sulfate (D))

[0179] The average particle size was measured using a laser diffraction particle size distribution measuring device (manufactured by Shimadzu Corporation, trade name "SALD-2100").

[0180] (Average fiber length, average fiber diameter, and aspect ratio of the reinforcing material (C))

[0181] The average fiber length, average fiber diameter, and aspect ratio of wollastonite or potassium titanate fibers were obtained by observing and measuring any 1000 average values ​​using a scanning electron microscope (SEM).

[0182] (Physical properties of particulate carbon materials (E))

[0183] The primary particle size of carbon black was obtained by using the arithmetic mean particle size (number mean), which is the average of the primary particle sizes measured by a transmission electron microscope (manufactured by Nippon Electron Co., Ltd., product model "JEM2010"). The DBP oil absorption was measured using a dibutyl phthalate absorber according to JIS K 6221. The BET specific surface area was measured according to JIS K 6217.

[0184] (Synthesis example 1)

[0185] Untreated wollastonite fibers were added to a Henschel mixer and treated with 1.0% by mass of octyltriethoxysilane relative to the untreated wollastonite fibers. The wollastonite fibers were then surface-treated by a dry method to prepare surface-treated wollastonite fibers (fibrous reinforcing material (C1)). It was confirmed that the average fiber length, average fiber diameter, and aspect ratio were the same as those of the untreated product.

[0186] (Synthesis example 2)

[0187] Except for replacing the untreated wollastonite fibers with untreated potassium titanate fibers, surface-treated potassium titanate fibers (fibrous reinforcing material (C1)) were prepared according to the same method as in Synthesis Example 1, and it was confirmed that the average fiber length, average fiber diameter and aspect ratio were the same as those of the untreated product.

[0188] (Synthesis example 3)

[0189] Except for replacing the untreated wollastonite fibers with untreated talc, surface-treated talc (plate-shaped reinforcing material (C2)) was prepared using the same method as in Synthesis Example 1, and it was confirmed that the average particle size was the same as that of the untreated product.

[0190] <Preparation of Liquid Crystal Polymer Compositions and Molded Liquid Crystal Polymer Articles>

[0191] (Examples 1 to 13 and Comparative Examples 1 to 4)

[0192] The liquid crystal polymer compositions were melt-blended using a twin-screw extruder at the proportions shown in Table 1 to produce granules. It should be noted that the barrel temperature of the twin-screw extruder was 330°C. Additionally, the untreated wollastonite fibers, untreated potassium titanate fibers, and untreated talc in Table 1 can be directly used from the aforementioned commercially available products.

[0193] The obtained granules were molded into two plates, plate 1 (90mm long, 50mm wide, and 3mm thick) and plate 2 (64mm long, 13mm wide, and 4mm thick), using an injection molding machine to obtain evaluation samples (liquid crystal polymer molded bodies). It should be noted that the barrel temperature of the injection molding machine was 330℃, and the mold temperature was 120℃.

[0194] <Evaluation>

[0195] (Hunter White)

[0196] The Hunter whiteness of the freshly molded plate 1 was measured using a colorimeter (manufactured by Nippon Denshoku Co., Ltd., trade name "ZE6000"). The results are shown in Table 1.

[0197] (Particle generation rate)

[0198] After measuring the weight of plate 2 using a precision balance (A&D Corporation, product model "GR-200"), it was placed on a reciprocating sliding test machine (evaluation device: Talk System Corporation, TK-1) and subjected to 200 reciprocating cycles with liquid crystal polyester resin (Rockwell hardness HRM53) as the material, under conditions of a travel distance of 20 mm, a load of 5 N, and a speed of 40 mm / s. After the sliding was completed, the particles adhering to plate 2 were removed with air, and the weight of plate 2 was measured again using a precision balance (A&D Corporation, product model "GR-200"). The weight difference before and after the test was taken as the amount of particles generated. The results are shown in Table 1.

[0199] (Sliding width and sliding depth of the sliding surface)

[0200] The surface of plate 2 after the particle generation test was observed using a 3D measuring microscope (manufactured by Keyence, product model "One-Shot VR-3100"), and the sliding width and sliding depth of the sliding surface were measured.

[0201] (Coefficient of friction)

[0202] Using a static friction testing machine (manufactured by Kyowa Interface Science Co., Ltd., product model "TRIBOSTAR TS 501"), a sliding test was conducted with a hard metal under the conditions of a load of 50g, a speed of 1mm / sec, a travel distance of 1mm, and a stainless steel ball (SUS304, Φ3mm). The static friction coefficient (μs) and dynamic friction coefficient (μk) of the plate 1 were measured. The results are shown in Table 1.

[0203] [Table 1]

[0204]

[0205] As shown in Table 1, in Examples 1 to 13, which used liquid crystal polymer compositions containing liquid crystal polymer (A), fluoropolymer (B), and reinforcing material (C), with at least a portion of the surface of the reinforcing material (C) covered by a treatment layer composed of a hydrophobic surface treatment agent, particle generation was suppressed, and the resulting liquid crystal polymer molded articles were able to reduce the coefficient of dynamic friction and the coefficient of static friction.

[0206] It is also known that: since the liquid crystal polymer molded body obtained in Example 1 is molded using fluoropolymer (B) (polytetrafluoroethylene resin), compared with the liquid crystal polymer molded body of Comparative Example 1 which is not molded using fluoropolymer (B), the amount of particles generated, the sliding width and / or sliding depth of the sliding surface and the coefficient of friction can be reduced, and the amount of particles generated can be significantly reduced.

[0207] Furthermore, it is known that since the liquid crystal polymer molded bodies obtained in Examples 3 and 9 are molded using barium sulfate (D) in addition to fluoropolymer (B), the sliding width of the sliding surface is further reduced compared with the liquid crystal polymer molded bodies of Examples 6 and 10 that are not molded using barium sulfate (D).

[0208] Furthermore, the Hunter whiteness of the liquid crystal polymer molded body of Example 3, which contains particulate carbon material (E), is 23.0, while the Hunter whiteness of the liquid crystal polymer molded body of Example 7, which does not contain particulate carbon material (E), is 81.5. The same applies when comparing Examples 9 and 11, which use surface-treated potassium titanate fibers. Therefore, it can be seen that by adding particulate carbon material, the Hunter whiteness is reduced, and the light-shielding performance is improved.

[0209] It is also known that in the liquid crystal polymer molded body obtained in Example 3, in addition to fluoropolymer (B) and barium sulfate (D), fibrous reinforcing material (C1) (wollastonite fiber) and plate-like reinforcing material (C2) (talc) with at least a portion of the surface covered by a treatment layer composed of a hydrophobic surface treatment agent were also used for molding. Compared with the liquid crystal polymer molded bodies of Examples 8 and 12 that were molded using only fibrous reinforcing material (C1) (wollastonite fiber), the amount of particles generated was reduced, and the sliding width and / or sliding depth of the sliding surface were further reduced.

[0210] Furthermore, it is known that in the liquid crystal polymer molded article obtained in Example 3, the surfaces of both the fibrous reinforcing material (C1) (wollastonite fiber) and the plate-like reinforcing material (C2) (talc) are covered by a treatment layer composed of a hydrophobic surface treatment agent. Therefore, compared with Example 13, where only the surface of the plate-like reinforcing material (C2) (talc) is covered by a treatment layer composed of a hydrophobic surface treatment agent, the coefficient of friction (especially the static coefficient of friction) can be further reduced. It should be noted that Example 13, where only the surface of the plate-like reinforcing material (C2) (talc) is covered by a treatment layer composed of a hydrophobic surface treatment agent, significantly reduces the coefficient of friction compared with Comparative Example 3, where neither the fibrous reinforcing material (C1) (wollastonite fiber) nor the plate-like reinforcing material (C2) (talc) undergoes surface treatment.

[0211] It can be seen that by molding a liquid crystal polymer composition containing liquid crystal polymer (A), fluoropolymer (B), a reinforcing material (C) whose surface is covered by a treatment layer composed of a hydrophobic surface treatment agent, and, if necessary, barium sulfate (D) and particulate carbon material (E), it is possible to reduce light shading, particle generation, sliding width and / or sliding depth of the sliding surface, as well as the dynamic and static friction coefficients, and in particular, to obtain an unexpected effect such as a significant improvement in particle suppression.

[0212] Therefore, liquid crystal polymer molded articles using the liquid crystal polymer composition of the present invention can be applied to, for example, optical electronic components constituting imaging modules.

Claims

1. A liquid crystal polymer composition, characterized in that: It contains a liquid crystal polymer (A), a fluoropolymer (B), and a reinforcing material (C). At least a portion of the surface of the reinforcing material (C) is covered by a treatment layer composed of a hydrophobic surface treatment agent. The reinforcing material (C) comprises both fibrous reinforcing material (C1) and plate-like reinforcing material (C2).

2. The liquid crystal polymer composition according to claim 1, characterized in that: The hydrophobic surface treatment agent is an alkoxysilane represented by the following general formula (I). ...Equation (I) In general formula (I), n represents any integer selected from 1 to 3, and R 1 R indicates alkyl, alkenyl, or aryl. 2 Indicates alkyl group.

3. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The average particle size of the fluororesin (B) is 0.1 μm to 100 μm.

4. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The content of the fluoropolymer (B) is 0.1% to 30% by mass in 100% by mass of the total liquid crystal polymer composition.

5. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The content of the reinforcing material (C) is 0.1% to 40% by mass in 100% by mass of the total liquid crystal polymer composition.

6. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The average fiber length of the fibrous reinforcing material (C1) is 1 μm to 300 μm.

7. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The fibrous reinforcing material (C1) has a Mohs hardness of 2.5 or higher and 5 or lower.

8. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The plate-shaped reinforcing material (C2) has a Mohs hardness of 1 or higher and less than 2.

5.

9. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The mass ratio of the plate-shaped reinforcing material (C2) to the fiber-shaped reinforcing material (C1), i.e., plate-shaped reinforcing material (C2) / fiber-shaped reinforcing material (C1), is 0.01 to 1.

10. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: At least a portion of the surfaces of both the fibrous reinforcing material (C1) and the plate-like reinforcing material (C2) is covered by a treatment layer consisting of a hydrophobic surface treatment agent.

11. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The liquid crystal polymer (A) is a fully aromatic liquid crystal polymer.

12. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The liquid crystal polymer composition is used in the imaging module.

13. A liquid crystal polymer molded article, characterized in that: The liquid crystal polymer molded body is a molded body of the liquid crystal polymer composition according to any one of claims 1 to 12.

14. The liquid crystal polymer molded article as described in claim 13, characterized in that: The liquid crystal polymer molded body is a component used in the imaging module.

15. An electrical and electronic device, characterized in that: The electrical and electronic equipment has a camera function. The electrical and electronic equipment has the liquid crystal polymer molded body as described in claim 13 or 14.

Citation Information

Patent Citations

  • The camera module

    JP2017513976A

  • Liquid crystal polymer composition, liquid crystal polymer molded article, and electrical / electronic device

    CN116438245A

  • Glass fiber reinforced polycarbonate resin composition with excellent die wear property

    JP2012188578A

  • Liquid composition

    WO2020241607A1